2018
DOI: 10.1167/tvst.7.5.31
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 9 Point-of-Care Immunoassay Result Predicts Response to Topical Cyclosporine Treatment in Dry Eye Disease

Abstract: PurposeWe evaluate a matrix metalloproteinase-9 (MMP-9) point-of-care immunoassay (InflammaDry) as a prognostic tool for topical cyclosporine treatment.MethodsA total of 20 healthy subjects and 40 patients meeting >3 dry eye disease (DED) criteria (ocular surface disease index [OSDI] score ≥ 12, tear film breakup time [TBUT] ≤10 seconds, Schirmer I test result ≤10 mm/5 minutes, corneal staining ≥1) were included. DED patients were treated with topical cyclosporine ophthalmic emulsion 0.05% twice daily for 1 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 31 publications
5
50
0
Order By: Relevance
“…These results are consistent with the results herein, which show that tear volume plays an important role in positive results generated by the MMP-9 immunoassay. A previous study examined the utility of the MMP-9 in-situ immunoassay for predicting responses to antiinflammatory treatments in dry eye patients with confirmed ocular surface inflammation 44 . The authors used semi-quantitative evaluation of band density to distinguish the severity of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the results herein, which show that tear volume plays an important role in positive results generated by the MMP-9 immunoassay. A previous study examined the utility of the MMP-9 in-situ immunoassay for predicting responses to antiinflammatory treatments in dry eye patients with confirmed ocular surface inflammation 44 . The authors used semi-quantitative evaluation of band density to distinguish the severity of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 participates in remodeling of the extracellular matrix after wounding of the corneal surface and is implicated in the pathogenesis of sterile corneal ulceration, ocular allergy, fungal keratitis, burns, advanced keratoconus with irregular surface, active pterygia, conjunctivochalasis, blepharitis, and dry eye [9][10][11][12][13][14][15][16] . In addition, MMP-9 levels in cases of dry eye or keratoconus are used to guide the decision to use anti-inflammatory treatments such as topical cyclosporine 9,17 . The MMP-9 immunoassay is a type of lateral flow immunoassay (LFIA).…”
mentioning
confidence: 99%
“…Normal MMP-9 levels (ng/ml) in human tears vary between 3 ng/ml and 40 ng/ml. The InflammaDry test has a sensitivity of 85% and a specificity of 94% in the detection of pathological levels of MMP-9 in tears [11] In previous studies, elevated levels of MMP-9 in patients with moderate to severe dry eye disease has been correlated with the severity and intensity of the symptoms and the corneal alterations of these patients, and the reduction in these with good response to the treatments [5] [6] [7]. MMP-9 plays a role in the regulation of corneal epithelial desquamation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a correlation between tear MMP-9 levels and the various clinical and anatomical parameters of dry eye, especially the Ocular surface disease index (OSDI), conjunctival staining and corneal staining. Several studies have also demonstrated a significant reduction in tear MMP-9 levels, indicated by a negative InflammaDry test, following different anti-inflammatory treatments such as corticosteroids, tacrolimus and topical cyclosporine [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the pathology of DE, from the initiation of tear hyperosmolarity in the early phase of DE, a vicious cycle of DE likely induces inflammatory processes and triggers the release of MMP-9 in a relatively late phase of DE [12]. As detection of elevated tear MMP-9 could be an ideal tool for diagnosis and management of DE, a tear MMP-9 immunoassay could be valuable to clinicians [13].…”
Section: Introductionmentioning
confidence: 99%